Sex-specific associations among infant food and atopic sensitizations and infant neurodevelopment - Rodriguez, Nicole; Tessier, Carmen A.; Mandhane, Piushkumar J.; Pei, Jacqueline; Simons, Elinor; Moraes, Theo J.; Turvey, Stuart E.; Subbarao, Padmaja; Kozyrskyj, Anita L. (Frontiers in Pediatrics, 2022)
Introduction: Food sensitization (FS) is a first and strong indicator of immune deviation in the progression to other allergic conditions. Sensitization to food or other allergens and related inflammation during critical windows of infant development may adversely affect neurodevelopmental milestones. However, additional research is needed to test this association further. Methods: Associations between atopic (any food or aeroallergen) or FS (specific to egg, soybean, peanut, and milk) at age 1 year and neurodevelopment up to 2 years of age were evaluated in the national CHILD Cohort Study, with a secondary aim of examining whether these associations were sex-specific. Sensitizations were assessed by skin prick tests (SPT) with neurodevelopment assessed using the cognitive, language, motor, and social-emotional subscales of the Bayley Scales of Infant Development (BSID-III). Results: Only socioemotional scores reached statistical significance among the four BSID-III domains. Sensitization at one year of age was associated with lower social-emotional scores, independent of the infant’s ethnicity. These findings were sex-specific and only observed among boys, among whom social-emotional scores were lowered by 5 points if atopic sensitization was present (-5.22 [95%CI: -9.96, -0.47], p=0.03) or if FS was present (-4.85 [95%CI: -9.82, 0.11], p=0.06). Similar results were observed using the standard SPT cut-off of ≥ 3mm — for atopic sensitization (-5.17 [95%CI: -11.14, -0.80], p=0.09) and for food sensitization (-4.61 [95%CI: -10.96, 1.74], p=0.15). Conclusion: In our study of term infants, we found an inverse, cross-sectional association between atopic and food sensitization status and social-emotional development scores in males but not females.